Effects of stingless bee (heterotrigona itama) honey on pathogenesis of depression in chronic unpredictable mild stress (CUMS) rat model - Zakaria, Fatin Haniza (2025)
In this study, the antidepressant effect of stingless bee honey (SBH) on chronic unpredictable mild stress (CUMS) in male Sprague Dawley rats and its mechanism of action were investigated. Rats were exposed to CUMS for 28 consecutive days by seven different stressors to induce depression. The stressor was triggered randomly to avoid habituation effects on the stressor. This study included five different groups; sham, DDH2O (1 ml/kg sterile double distilled water), PRX (10 mg/kg paroxetine), SBH D15 (SBH 2000 mg/kg), and SBH D1 (SBH 2000 mg/kg). Each of the groups comprised six individuals (n=6). DDH2O, PRX and SBH D15 were administered with their respective treatment once daily starting from day 15 to day 28, while SBH D1 was administered SBH from the first day to day 28 CUMS induction. At the end of the CUMS induction protocol, rats were subjected to a sucrose preference test (SPT), forced swimming test (FST), and Morris water maze (MWM), followed by biochemical examination (serum) and histopathological analysis (hippocampus brain). All CUMS induced groups successfully induced depressive like behaviour by showing a decrease in food intake, body weight gain, percentage of sucrose preference in SPT, increased immobility in the FST, shorter latency finding platform (MWM), and higher retention time spent in the target quadrant (MWM) when compared to the sham group. The positive control group (PRX) and both SBH groups (SBH D15 and SBH D1) were shown to attenuate depressive like behaviour in comparison to the untreated group CUMS (DDH2O). The CUMS induced groups were also found to have higher dopamine (DA) levels, lower serotonin (5HT) and lower GABA levels compared to the sham group. PRX and both SBH groups (SBH D15 and SBH D1) showed positive progression in all analyzed neurotransmitters in the current study, compared to the DDH2O group. In addition, serum was analysed for eight different interleukin cytokines and inflammatory markers (IL 4, IL 5, IL 10, IL 13, IL 6, IL 2, IL 1β, and TNF α). DDH2O showed high levels of all markers compared to the other groups. PRX and both SBH groups (SBH D15 and SBH D1) showed attenuation of inflammation. Brain tissues in the hippocampus regions (Cornu ammonis 1 (CA1), Cornu ammonis 3 (CA3) and Dentate Gyrus (DG)) for analysis of the optical density of IHC expression of BDNF, DDH2O group showed the lowest optical density expression of BDNF compared to other groups. Meanwhile, PRX and both SBH groups (SBH D15 and SBH D1) showed a positive elevation of the optical density of BDNF expression. In conclusion, both SBH groups showed an improvement in ameliorating the pathogenesis of depression after being induced with depression via CUMS paradigms for 28 days, compared to the DDH2O group. All results indicated that SBH provides synergistic effects to elevate the monoamine parameters as well as suppress the inflammatory cytokines that eventually improve the behaviour output of depressed rats.